ELIMINATION OF SOME UNKNOWN PARAMETERS AND ITS EFFECT ON OUTLIER DETECTION - Hekimoglu, Serif; Erdogan, Bahattin; Tunalioglu, Nursu (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2012)
Outliers in observation set badly affect all the estimated unknown parameters and residuals, that is because outlier detection has a great importance for reliable estimation results. Tests for outliers (e.g. Baarda's and Pope's tests) are frequently used to detect outliers in geodetic applications. In order to reduce the computational time, sometimes elimination of some unknown parameters, which are not of interest, is performed. In this case, although the estimated unknown parameters and residuals do not change, the cofactor matrix of the residuals and the redundancies of the observations change. In this study, the effects of the elimination of the unknown parameters on tests for outliers have been investigated. We have proved that the redundancies in initial functional model (IFM) are smaller than the ones in reduced functional model (RFM) where elimination is performed. To show this situation, a horizontal control network was simulated and then many experiences were performed. According to simulation results, tests for outlier in IFM are more reliable than the ones in RFM.
Keywords: Elimination; Tests for Outliers; Reliability; Adjustment; TESTS; Geochemistry & Geophysics; Remote Sensing